Polimorfismo do RRE e resistência aos antirretrovirais do vírus da imunodeficiência humana e efeito citopático e replicativo in vitro da enfuvirtida no códon 36 do vírus modificado pNL4-3 - Medeiros, Melissa Soares (2011)
Introduction: Rev Responsive Element (RRE) is a RNA molecule responsible to mRNA from HIV-1 virus nuclear transportation to cytoplasm through RRE-Rev pathway, essential to virus replication. Enfuvirtide resistance mutations are primary located in a perimeter of 10 amino acids of HR1, a corresponded region of RRE. Characterize RRE should provide a new approach for HIV therapy. Objectives: Sequence and characterize RRE from gp41 to evaluate variability and correlate with laboratory parameters in sequences from HIV-1-infected patients, which were receiving regimens including Enfuvirtide, naïve or rescue therapy. Also evaluated mutation G to D at codon 36 in the presence of fusion inhibitor (enfuvirtide). Methods: Sixty-two samples from HIV patients in Ceara/Brazil were collected and Thirty-five RRE sequences and clinical follow-up were analyzed, distributed into three groups: N (naïve therapy), T (treated patients with rescue regimens) and F (rescue regimens containing Enfuvirtide). Sequences obtained were aligned with Los Alamos HIV sequence database by using the HIV BLAST Search. Culture Study was performed using two different pNLA-3 (36D and 36G) with increasing amounts of enfuvirtide. Results: A phylogenetic analyses demonstrated higher prevalence of HIV-1 subtypes B (97.2%). An increased immunology response was observed in CD4 count higher on group T (71.5%) compared with F (2.98%). Group N most common mutations and polymorphisms were Q32L (41.6%), N42S (8.3%), R46K (33.3%), L54M (41.6%); group T: Q32R (8.3%), R46K (25%), L54M (33.3%); and group F: Q32L (18.2%), G36D (9.1%), V38A (9.1%), N42S (27.3%), N42T (9.1%), R46K (27.3%), L54M (45.4%), K77R (54.5%). Three samples demonstrated significant resistance mutations to fusion inhibitors. Analysis of RRE nucleotide primary sites observed mutation 28A in 27.2% and 8.3% on groups F and N respectively, and 27S in 8.3% on group T. There was selective pressure on HR1 region from HIV-1 patients using antiretroviral, independent of enfuvirtide exposure. There was no statistical difference between p24 curves of virus 36D compared with 36G, independent of T20 concentrations (p>0.05). It was observed less syncytial formation in 36D virus, with diminished fusogenic activity besides keeping infectivity. Conclusions: This study defined most prevalent RRE polymorphisms in Ceara/Brazil and suggests highly preserved regions primary sites to Rev connection. Observed a low resistance profile to enfuvirtide in failing regimens with this drug. Selective pressure on HR1 region in failed regimens with out fusion inhibitors was detected. A less syncytial formation in 36D virus with diminished fusogenic activity was detected.